Modified Cox maze procedure for atrial fibrillation with mitral valve disease - Montien Ngodngamthaweesuk (2018)
Objective: To determine early term results of the modified Cox maze procedure for curing atrial fibrillation (AF) associated with mitral valve disease. Method: Between January and December 2000, 10 consecutive patients with AF underwent the modified Cox maze procedure with mitral valve repair in 2 and replacement in 8. The associated procedure included 3 aortic valve replacements, 1 tricuspid annuloplasty, and 2 atrial septal defect closures. There were 5 males and 5 females, with ages ranging from 19 to 52 years (mean = 38.3 years). Pre-operative-existing AF time varied from 4 to 146 months (mean = 41.1 months), and left atrial dimension varied from 4.50 to 6.89 cm (mean 5.51 cm). The authors modified the maze atriotomies to preserve the sinus node artery and used cryoablation, incision and suture to simplify the procedures. Results: Seven cases (70%) regained sinus rhythm and 3 cases (30%) still remained in AF. Two cases (double valve replacement) needed intraaortic balloon pump. Two of them developed cardiac tamponade 1 month post-operatively, (one in sinus rhythm case and another one in AF). Those 3 patients who remained in AF had a longer pre-operative existing AF-time and larger left atrial dimension but it was insignificant (p = 0.227 and p = 0.187 respectively). There was no early or late mortality. Conclusion: The pertaining results suggest that the modified Cox maze procedure has satisfactory effectiveness to cure atrial fibrillation, restore atrioventricular synchrony and preserve atrial transport function in the patients having AF associated with mitral valve disease.